Basic Principles of Membrane Technology - Mulder, Marcel (Springer Netherlands, 1996)
The field of synthetic membrane science and technology is an active, growing field involving an interdisciplinary mixture of polymer chemistry, physical chemistry, and chemical engineering. Some membrane processes are reasonably well understood, and have been commercialised for some period of time. Other membrane processes have only recently been employed in commercial applications, and still other processes are only in formative research stages. This volume gives a comprehensive compendium of the basic principles in the field of synthetic membranes. The following topics are covered: basic aspects of membrane processes; materials and material properties; membrane preparation and characterisation; membrane transport; concentration polarisation and fouling; process and module design. The second edition of this well-established text has been considerably expanded and updated, and many chapters now contain sections giving solved and unsolved problems. Audience: This book is recommended as a textbook for undergraduate and graduate students, as well as a comprehensive reference for engineers, scientists, and technical management.